Antioxidant Properties and Textural Characteristics of Processed Cheese Spreads Enriched with Rutin or Quercetin: the Effect of Processing Conditions - Přikryl, Jakub; Hájek, Tomáš; Švecová, Blanka; Salek, Richardos Nikolaos; Černíková, Michaela; Červenka, Libor; Buňka, František (My University, 2018)
Spreadable processed cheese (SPC) with addition of rutin or quercetin (0.5 g/100 g) were prepared at 80 °C and 90 °C for 1, 5 and 10 min. The effect of melting temperature and holding time of melting temperature on the quercetin/rutin retention, total phenolic content (TPC) and antioxidant capacity was studied. It was found that quercetin levels significantly decreased with the increase of holding time (P<0.01) while rutin degradation was more affected by melting temperature (P<0.01). An increase in TPC values and a decrease in antioxidant capacity measured by ABTS assay with the increase in melting temperature were observed in SPC with quercetin. The addition of rutin or quercetin significantly decreases the gel strength of the SPC samples.
Antioxidační vlastnosti a texturní charakteristika taveného sýra obohaceného rutinem nebo kvercetinem: vliv technologických podmínek
Keywords: processed cheese; flavonoids; melting condition; antioxidants; Tavený sýr; flavonoidy; tavící proces; antioxidanty